Epidemiological, clinical, and therapeutic profile of tuberculosis in a high-burden Latin American capital: Tegucigalpa, Honduras - Carías, Alejandro; Vega, Lourdes Carolina; Carías, Pablo; Auza-Santivañez, Jhossmar Cristians; Robles-Nina, Sara Milca; Bautista-Vanegas, Freddy Ednildon; Cabezas Soliz, Ingrid Neysa; Antezana-Muñoz, Jose Bernardo; Gómez-Triana, Jaykel Evelio (Salud Integral y Comunitaria, 2026)
Introduction: Tuberculosis (TB) remains a major public health problem in Honduras, particularly in urban areas such as Tegucigalpa. Identifying clinical and epidemiological patterns helps guide control strategies. Objective: To describe the sociodemographic, clinical, and treatment outcome characteristics of patients diagnosed with TB in Tegucigalpa between 2022 and 2024. Methods: A descriptive, retrospective study was conducted with 165 patients diagnosed with TB. Data on sociodemographics, medical history, diagnostic methods, type of TB, treatment regimen, and discharge condition were collected. Analysis was performed using frequencies and percentages. Results: Males accounted for 61.2% of patients. Unemployed individuals represented 15.8%, prisoners 14.5%, and housewives 8.5%. A total of 14.5% had completed preschool education, and another 14.5% had no formal education. The most common comorbidity was diabetes mellitus (11.5%), followed by diabetes mellitus/hypertension (8.5%). The most frequent diagnostic method was smear microscopy (80.6%). Pulmonary TB accounted for 97.6% of cases. Basic treatment was administered to 96.4% of patients. Cure rate was 84.8%, with 3.6% relapses and 1.8% deaths. Conclusion: Most TB cases in Tegucigalpa occurred in adult men with low education levels and chronic comorbidities such as diabetes. Diagnosis was mainly through smear microscopy, with a high cure rate, though challenges remain in relapse monitoring and prevention in vulnerable populations.